2010 Asia-Pacific Power and Energy Engineering Conference 2010
DOI: 10.1109/appeec.2010.5448640
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on Energy Consumption and Optimal Operation of FGD System in Power Plant

Abstract: This paper analyzed the energy consumption characteristics of typical limestone-gypsum wet flue gas desulfurization (FGD) system which is widely used in power plant for SO x removal, and discussed its optimal operation. In the FGD system, booster fan; circulating slurry pump and oxidation fan are three major energy consuming devices. We established the mathematical models to disclose the relationship between the energy consumption and the desulfurization features of these equipments. On this basis, we obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…First, this work explored emission mitigation pathways based on national strategies without the consideration of economic costs, such as replacement costs of new power units and costs of control device upgrades. Second, electric energy is consumed to make end-of-pipe control measures operate, which is not included in the total coal-fired electricity demand in this work. A set of sensitivity test scenarios on conventional end-of-pipe controls (de-SO 2 , de-NO x , and de-PM devices) shows that additional 2% energy consumption from end-of-pipe controls have a minor effect on air pollutants and CO 2 emissions increasing by 0.5–2.3% during 2015–2030 (Figure S6).…”
Section: Discussion and Policy Implicationsmentioning
confidence: 99%
“…First, this work explored emission mitigation pathways based on national strategies without the consideration of economic costs, such as replacement costs of new power units and costs of control device upgrades. Second, electric energy is consumed to make end-of-pipe control measures operate, which is not included in the total coal-fired electricity demand in this work. A set of sensitivity test scenarios on conventional end-of-pipe controls (de-SO 2 , de-NO x , and de-PM devices) shows that additional 2% energy consumption from end-of-pipe controls have a minor effect on air pollutants and CO 2 emissions increasing by 0.5–2.3% during 2015–2030 (Figure S6).…”
Section: Discussion and Policy Implicationsmentioning
confidence: 99%
“…(5) Most of the pollution reduction solutions currently used, such as FGD technology for SO 2 abatement, are end-of-pipe control solutions which generally increase energy consumption. According to Xu et al (2010), 1.1-1.5% of the power plant's electricity production is needed for FGD operation. Consequently, they increase emissions of CO 2 to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, different works have shown that many pollutants, specifically sulfur compounds, can greatly harm the cell units [18][19][20][21]. The units implemented within this design were selective catalytic reduction and wet limestone scrubbing for flue gas pre-treatment for Nitrogen Oxides (NOx) [22,23] and Sulphur Dioxide (SO2) respectively [24][25][26]. A detailed assessment of differing removal methods was not considered within this project scope and so the selection of these unit methods was a result of industrial prevalence and applicability to the process system.…”
Section: Examination Of the Mcfc Integrated Plant Environmentmentioning
confidence: 99%